Aerobic Tofu Industrial Wastewater Treatment Installation Planning Using Rotating Biological Contractors (RBC) (Case Study at "Sari Murni" Tofu Factory, Krajan Village, Mojosongo Village, Surakarta City) - Yonathan Suryo Pambudi; Cicik Sudaryantiningsih; Virgianto Tara Amah; John Tunggu Jama; Ripi (East Asian Journal of Multidisciplinary Research, 2022)
The planned advanced processing technology is aerobically using Rotating Biological Contactors (RBC). The research method used was la iterature study, in-depth interviews, and direct observation to the Sari Murni tofu factory to determine the existing conditions of the existing Wastewater Treatment Plant (IPAL), as well as to determine the discharge and characteristics of the tofu wastewater. From the results of observations in the field, it is known that the maximum discharge of tofu wastewater produced every day is 25 m3 with an average BOD parameter value of 200 mg/L. Furthermore, the researchers calculated the required RBC dimensions so that the BOD parameter value could be below standard (<150 mg/L). Based on the calculation results, it can be seen that the surface area of ​​the Rotating Biological Contractors (RBC) required is 450 m2, the number of disks required is 131 pieces, and the length of the Rotating Biological Contractors (RBC) rotor required is 2.5 meters.